Buy Now, Worry Later? Analisis Motivasi dan Preferensi Pengguna Pay later terhadap Consumer Spending Decision - Anni Safitri; Mar'atus Sholikah (Politeknik Raflesia Press, 2025)
Pay later use is increasingly popular today, but there is no research specifically investigating the influence of shopping motivations and pay later preferences on consumer spending decisions. However, this is a highly interesting topic to explore to create a healthier, more responsible and smarter shopping environment. Quantitative research and data collection techniques using online surveys via Google Form are used in this study. The findings of this study indicate that utilitarian and hedonic motivations have a positive and significant effect on consumer spending decisions through the pay later payment mode. Perceived convenience has no effect on pay later user preferences, while perceived trust has an effect on consumers' decisions to pay later. Overall, motives and trust influence the purchase decision, while hedonics have a stronger influence.